Nine true bugs (Heteroptera) newly-discovered in Illinois - Swanson, Daniel R.; Taylor, Steven J.; Heads, Sam W. (Zootaxa, 2017)
Six heteropteran species are reported for the first time from Illinois based on recently caught specimens from various bioinventories: the flat bug Neuroctenus pseudonymus Bergroth (Aradidae: Mezirinae), the stilt bug Metacanthus multispinus (Ashmead) (Berytidae: Metacanthinae), the leaf-footed bugs Anasa repetita Heidemann and Chelinidea vittiger Uhler (Coreidae: Coreinae), the ambush bug Phymata fasciata fasciata (Gray) (Reduviidae: Phymatinae), and the scentless plant bug Arhyssus nigristernum (Signoret) (Rhopalidae: Rhopalinae). Additionally, three more records for the flat bug Nannium pusio Heidemann (Aradidae) and the scentless plant bugs Aufeius impressicollis Stål and Niesthrea louisianica Sailer (Rhopalidae) are newly-reported for the state based on material in the Illinois Natural History Insect Collection (INHS). Supplementing these notes are dichotomous keys to the species of Mezirinae, Berytidae, Coreidae, Phymatinae, and Rhopalidae of Illinois.